OCEANOGRAPHIC DATA OF THE 26TH JAPANESE ANTARTIC RESEARCH EXPEDITION FROM NOVEMBER 1984 T0 APRIL 1985 - イワナミ, ケイスケ; トウジュ, ヒロシ; IWANAMI, Keisuke; TOHJU, Hiroshi (National Institute of Polar Research, 1987)
P(論文) This report presents the data of the oceanographic observations on board the icebreaker Shirase and the tidal observation at Syowa Station, which were carried out in the summer mission of the 26th Japanese Antarctic Research Expedition in 1984-1985. departmental bulletin paper